Strategi perbankan syariah dalam menghadapi risiko pembiayaan bermasalah - Fatihah, Ramadina Salwanda (Maliki Interdisciplinary Journal, 2025)
This research aims to examine the strategies implemented by Islamic banks in dealing with problematic financing through a qualitative descriptive approach based on literature review, using 6 previous studies as a reference. The results of the study from six articles show that Islamic banks’ strategies in dealing with problematic financing include preventive and curative approaches. The preventive approach is carried out through strict screening and analysis of prospective customers using the 5C+1S criteria (character, capacity, capital, collateral, conditions and sharia compliance) to reduce risk from the start. Apart from that, a curative approach is used when financing has failed, through resolving financing in the form of rescheduling, changing conditions (reconditioning) and rearranging the contract (restructuring). If this strategy is not effective, the bank can carry out legal settlements, execute collateral, and even write-off without abandoning sharia principles.